Workplace Assessment of Targeted Violence Risk: The Development and Reliability of the WAVR‐211. Issue 5 (18th July 2013) - Meloy, J. Reid; White, Stephen G.; Hart, Stephen
Abstract: This study describes the development of the WAVR‐21, a structured professional judgment guide for the assessment of workplace targeted violence, and presents initial interrater reliability results. The 21‐item instrument codes both static and dynamic risk factors and change, if any, over time. Five critical items or red flag indicators assess violent motives, ideation, intent, weapons skill, and pre‐attack planning. Additional items assess the contribution of mental disorder, negative personality factors, situational factors, and a protective factor. Eleven raters each rated 12 randomly assigned cases from actual files of workplace threat scenarios. Summary interrater reliability correlation coefficients (ICCs) for overall presence of risk factors, risk of violence, and seriousness of the violent act were in the fair to good range, similar to other structured professional judgment instruments. A subgroup of psychologists who were coders produced an ICC of 0.76 for overall presence of risk factors. Some of the individual items had poor reliability for both clinical and statistical reasons. The WAVR‐21 appears to improve the structuring and organizing of empirically based risk‐relevant data and may enhance communication and decision making.